Current Trends in Donor Testing to Detect Syphilis Infection - Cortez, Karoll J.; Greenwald, Melissa A. (Current infectious disease reports, 2014)
Potential organ and tissue donors are tested to detect infection with T. pallidum , the etiologic agent of syphilis. Important considerations for testing potential donors include available specimen type and volume, turnaround time, and ability to distinguish between past and current infection. Aspects of syphilis infection that inform organ and tissue donor assay selection and interpretation and the principles underlying available assays are described. Serologic assays for syphilis are the methods most commonly used in donor testing. The two categories of serologic assays, treponemal and nontreponemal, have advantages and limitations for testing potential donors. Knowledge of the common syphilis-testing algorithms used in clinical diagnostic testing is useful for assay selection in the organ and tissue donor setting.